Successful Function-Preserving Therapy for Chondroblastoma of the Temporal Bone Involving the Temporomandibular Joint - Yokoyama, Junkichi (S. Karger AG, 2011)
We present a case involving a late diagnosis of chondroblastoma of the temporal skull base involving the temporomandibular joint (TMJ). Following an initial misdiagnosis and unsuccessful treatment over a period of 5 years, the patient was referred to our department for further evaluation and possible surgical intervention for occlusal abnormalities, trismus, clicking of the TMJ, and hearing impairment. Based on preoperative immunochemical studies showing positive reaction of multinucleated giant cells for S-100 protein, the final diagnosis was chondroblastoma. The surgical approach – postauricular incision and total parotidectomy, with complete removal of the temporal bone, including the TMJ via the extended middle fossa – was successful in preserving facial nerves and diminishing clinical manifestations. This study highlights a misdiagnosed case in an effort to underline the importance of medical examinations and accurate differential diagnosis in cases involving any tumor mass in the temporal bone.